Handbook of twentieth-century literatures of India - Natarajan, Nalini; Nelson, Emmanuel S. (Emmanuel Sampath) 1954- (Gale virtual reference library, 1996)
Surveys the major regional literatures of contemporary India in the context of the country's diversity and heterogeneity. Focuses on literatures written in languages other than English, rather than the more commonly studied English-language postcolonial works.